2018
DOI: 10.1101/490201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How long do Red Queen dynamics survive under genetic drift? A comparative analysis of evolutionary and eco-evolutionary models

Abstract: Background: Red Queen dynamics are defined as long term co-evolutionary dynamics, often with oscillations of genotype abundances driven by fluctuating selection in host-parasite systems.Much of our current understanding of these dynamics is based on theoretical concepts explored in mathematical models that are mostly (i) deterministic, inferring an infinite population size and (ii) evolutionary, thus ecological interactions that change population sizes are excluded. Here, we recall the different mathematical a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…(2009) found that genetic variation is not maintained at equilibrium except when mutation is very frequent. This is echoed in simulations in finite populations, where in the absence of mutation/migration, fixation in either the host or pathogen is vary rapid (Gokhale et al, 2013;Schenk et al, 2018). In addition to including mutation, there are several theoretical indications that, rather than being driven by NFDS, the emergent 45 effects of coevolution are dependent on the existence of heterozygote advantage in diploids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) found that genetic variation is not maintained at equilibrium except when mutation is very frequent. This is echoed in simulations in finite populations, where in the absence of mutation/migration, fixation in either the host or pathogen is vary rapid (Gokhale et al, 2013;Schenk et al, 2018). In addition to including mutation, there are several theoretical indications that, rather than being driven by NFDS, the emergent 45 effects of coevolution are dependent on the existence of heterozygote advantage in diploids.…”
Section: Introductionmentioning
confidence: 99%
“…Here we compare the maintenance of genetic variation in finite coevolving populations relative to that expected under neutral drift. Previous studies of finite coevolving populations have focused instead on the number of alleles maintained by mutation and coevolution (Borghans et al, 2004), the time until loss 55 of alleles (Gokhale et al, 2013), and the impact of different model assumptions on the time until loss (Schenk et al, 2018). A direct comparison with the neutral expectation is, however, only possible analytically in simple models of host-parasite coevolution.…”
mentioning
confidence: 99%